Phenolic glucosides from the leaves of Desmodium gangeticum (L.) DC - Dat, Nguyen Tien; Luyen, Nguyen Thi; Dang, Nguyen Hai (Vietnam Journal of Chemistry, 2015)
From the water-soluble extract of the leaves of Desmodium gangeticum, three phenolic glucosides were isolated. By means of spectroscopic methods they were identified as methyl salicylate β-D-glucopyranoside (1), leonuriside A (2) and syringaresinol-4'-O-β-D-glucopyranoside (3). These compounds were isolated for the first time from the genus Desmodium. Compound 1 significantly inhibited a-glucosidase in comparison with diabetic drug acarbose.